Effects of Sex and Age on Serum 1,5-anhydroglucitol in Nondiabetic Subjects - Ouchi, M.; Oba, K.; Yamashita, H.; Okazaki, M.; Tsunoda, M.; Ohara, M.; Sekimizu, K.; Watanabe, K.; Suzuki, T.; Nakano, H. (Experimental and Clinical Endocrinology & Diabetes, 2012)
The aim of this study was to demonstrate the effects of sex and age on serum levels of 1,5-AG in nondiabetic subjects.A total of 1 134 nondiabetic subjects aged 16–96 years with HbA1c less than 6.8% were recruited and divided into 4 HbA1c groups (Q1: HbA1c≤5.3; Q2: 5.4–5.8; Q3: 5.9–6.3; and Q4: 6.4–6.8 [%]). 38 elderly subjects (65 years or older) in the Q3 and Q4 groups (13 men and 25 women) underwent a 75-g oral glucose tolerance test (OGTT).The Q4 group had significantly lower 1,5-AG levels than did the Q1 group among nonelderly males, nonelderly females, and elderly men. In elderly women, 1,5-AG levels did not differ among the 4 HbA1c groups. In both nonelderly and elderly subjects, the 1,5-AG level of the Q1 group was significantly higher in males than in females. Stepwise multivariate regression analysis showed that age was significantly associated with 1,5-AG level in both sexes. HbA1c was significantly associated with the 1,5-AG level in males, while there was no significant association between HbA1c and the 1,5-AG level in females. In the elderly OGTT group, although the glucose levels of both sexes during OGTT were identical, the mean urinary glucose levels and the percentages of subjects with glucosuria were significantly higher in elderly men than in elderly women.Serum 1,5-AG levels were significantly associated with age and sex. The sensitivity of the 1,5-AG level for identifying postprandial hyperglycemia in elderly women with near-normoglycemia is less reliable because they have a higher renal threshold for glucose.
Keywords: 1,5-anhydroglucitol; renal threshold; glucosuria; age; sex; nondiabetics